Clinical improvement and reduction in serum calprotectin levels after an intensive exercise programme for patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis - Levitova, Andrea; Hulejova, Hana; Spiritovic, Maja; Pavelka, Karel; Senolt, Ladislav; Husakova, Marketa (Arthritis research & therapy, 2016)
BACKGROUND: The efficacy of exercise therapy for ankylosing spondylitis (AS) is well-documented, but dearth of information is for non-radiographic axial spondyloarthritis (nr-axSpA). Biomarkers like serum calprotectin, interleukins IL-6, IL-17 and tumour necrosis factor (TNF)-α may reflect the disease activity of axial spondyloarthritis (axSpA). In this study, we investigated clinical and laboratory parameters of both axSpA subgroups in response to intensive physical exercise. METHODS: Altogether, 46 patients with axSpA, characterised according to the Assessment of SpondyloArthritis International Society criteria as having nr-axSpA or AS underwent 6-month exercise programme. Clinical outcomes of disease activity, Bath AS Disease Activity Index (BASDAI), AS Disease Activity Index (ASDAS-CRP), mobility, Bath AS Metrology Index (BASMI) and function, Bath AS Functional Index (BASFI) were evaluated at baseline and at the end of the exercise programme. Serum IL-6 and IL-17, TNF-α and calprotectin were measured via ELISA. The clinical and laboratory data of 29 control axSpA patients were used for the evaluation of the results. RESULTS: In all axSpA patients, the ASDAS-CRP (2.10 ± 0.12 to 1.84 ± 0.11, p <0.01) and BASMI (1.28 ± 0.14 to 0.66 ± 0.84, p <0.0001) improved after 6 months of exercise therapy. There was a significant improvement in the ASDAS-CRP in the nr-axSpA subgroup (2.01 ± 0.19 to 1.73 ± 0.16, p <0.05) and in the BASMI in both, the nr-axSpA and the AS subgroups (1.09 ± 0.12 to 0.47 ± 0.08, p <0.0001 and 1.43 ± 0.24 to 0.82 ± 0.23, p <0.0001, respectively). Both, ASDAS-CRP and BASDAI, were significantly improved in the exercise axSpA group compared to the control axSpA group (mean -0.26 vs. -0.13 and -0.49 vs. 0.12, respectively, all p <0.05). Only calprotectin was significantly reduced after the exercise programme in nr-axSpA and AS patients (from 2379.0 ± 243.20 to 1779.0 ± 138.30 μg/mL and from 2430.0 ± 269.70 to 1816.0 ± 148.20 μg/mL, respectively, all p <0.01). The change in calprotectin was more profound in the axSpA intervention group (mean -604.56) than in the control axSpA (mean -149.28, p <0.05). CONCLUSION: This study demonstrated similar efficacy for an intensive exercise programme in both nr-axSpA and AS patients. A significant decrease in serum calprotectin levels in both subgroups of axSpA patients after the exercise programme reflected an improvement in the disease activity and spinal mobility.
Keywords: Spondylarthritis; imunoanalýza; Immunoassay; mužské pohlaví; Adult; Leukocyte L1 Antigen Complex; Exercise programme; ankylózující spondylitida; leukocytární L1-antigenní komplex; Non-radiographic; ženské pohlaví; ELISA; Spondylitis, Ankylosing; Humans; Disease activity; Ankylosing spondylitis; biologické markery; spondylartritida; terapie cvičením; Exercise Therapy; Enzyme-Linked Immunosorbent Assay; dospělí; Biomarkers; Female; Calprotectin; Axial spondyloarthritis; lidé; Male